Comparative genetic analyses of Human Rhinovirus C (HRV-C) complete genome from Malaysia - Yam, Sim Khaw; Yoke, Fun Chan; Jafar, Faizatul Lela; Othman, Norlijah; Hui, Yee Chee (Frontiers, 2016)
Human rhinovirus-C (HRV-C) has been implicated in more severe illnesses than HRV-A and HRV-B, however, the limited number of HRV-C complete genomes (complete 5' and 3' non-coding region and open reading frame sequences) has hindered the in-depth genetic study of this virus. This study aimed to sequence seven complete HRV-C genomes from Malaysia and compare their genetic characteristics with the 18 published HRV-Cs. Seven Malaysian HRV-C complete genomes were obtained with newly redesigned primers. The seven genomes were classified as HRV-C6, C12, C22, C23, C26, C42, and pat16 based on the VP4/VP2 and VP1 pairwise distance threshold classification. Five of the seven Malaysian isolates, namely, 3430-MY-10/C22, 8713-MY-10/C23, 8097-MY-11/C26, 1570-MY-10/C42, and 7383-MY-10/pat16 are the first newly sequenced complete HRV-C genomes. All seven Malaysian isolates genomes displayed nucleotide similarity of 63-81% among themselves and 63-96% with other HRV-Cs. Malaysian HRV-Cs had similar putative immunogenic sites, putative receptor utilization and potential antiviral sites as other HRV-Cs. The genomic features of Malaysian isolates were similar to those of other HRV-Cs. Negative selections were frequently detected in HRV-Cs complete coding sequences indicating that these sequences were under functional constraint. The present study showed that HRV-Cs from Malaysia have diverse genetic sequences but share conserved genomic features with other HRV-Cs. This genetic information could provide further aid in the understanding of HRV-C infection.